Enhanced Photocatalytic Activity and Photoluminescence of ZnO Nano-Wires Coupled with Aluminum Nanostructures - Mondher Rtimi; Nour Beydoun; Artur Movsesyan; Suzanna Akil; Sergei Kostcheev; Xavier Gassmann; Mohamed Lajnef; Radhouane Chtourou; Safi Jradi (Nanomaterials, 2022)
In this study, we fabricated a hybrid plasmonic/semiconductor material by combining the chemical bath deposition of zinc oxide nanowires (ZnONWs) with the physical vapor deposition of aluminum nanostructures (AlNSs) under controlled temperature and atmosphere. The morphological and the optical properties of the ZnONWs/AlNSs hybrid material fabricated at different temperatures (250, 350, and 450 °C) and thicknesses (5, 7, and 9 nm) of Al layers were investigated. By adjusting the deposition and annealing parameters, it was possible to tune the size distribution of the AlNSs. The resonant coupling between the plasmonic AlNSs and ZnONWs leads to an enhanced photoluminescence response. The photocatalytic activity was studied through photodegradation under UV-light irradiation of methylene blue (MB) adsorbed at the surface of ZnO. The MB photodegradation experiment reveals that the ZnONWs covered with 7 nm aluminum film and annealed at 450 °C exhibit the highest degradation efficiency. The comparison between ZnONws and ZnONws/AlNSs shows a photoluminescence enhancement factor of 1.7 and an increase in the kinetics constant of photodegradation with a factor of 4.